Protonic ceramic fuel cells for power-ethylene cogeneration: A modelling study on structural parameters. (1st February 2023) - Li, Zheng; He, Qijiao; Wang, Chen; Yu, Na; Bello, Idris Temitope; Guo, Meiting; Ni, Meng
Abstract: Protonic ceramic fuel cells (PCFCs) are promising electrochemical devices to achieve power-ethylene cogeneration. A model of a tubular C2 H6 -fed PCFC, including an internal reforming section (IRS) and an electrochemical reaction section (ERS), is constructed to investigate the effects of structural parameters on the cogeneration performance. Increasing cell length and ERS markedly enhance the ethylene yield. The highest ethylene yield of 44% is obtained in a 10 cm PCFC at 973 K. The positive effect of thickening the entire anode or IRS on yield is not as pronounced as extending the cell length or ERS. Except that the increase of IRS thickness leads to the decrease of the current density, the increase of other structural parameters causes the current density to increase first and then decrease. By decreasing the ERS ratio, the current density can be enhanced up to 14% and reaches the highest value of 2235 A m −2 at 973 K in an 8 cm PCFC with a 30% ERS ratio. This model provides an insightful understanding of the interrelationship between the structural parameters and the cogeneration performance of PCFC. This model can also serve as a valuable tool for the PCFC fuelled with other hydrocarbons. Highlights: A 2D asymmetric model for tubular C2 H6 -PCFC is constructed. The effects of structural parameters on PCFC performance are quantitatively studied. Increasing cell length by 1 cm can enhance ethylene yield by 12.5%. Increasing ERS ratio by 10% can enhance ethylene yield by 7.7%. Increasing IRS thickness by 100 μm can decrease current density by 6.3%.